2014
DOI: 10.1080/01652176.2014.966172
|View full text |Cite
|
Sign up to set email alerts
|

Loop-mediated isothermal amplification (LAMP) test for specific and rapid detection ofBrucella abortusin cattle

Abstract: The novelty of the developed LAMP assay for specifically detecting B. abortus infection in cattle along with its inherent rapidness and high sensitivity can be employed for detecting this economically important pathogen of cattle at field level as well be exploited for screening of human infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 27 publications
0
40
0
Order By: Relevance
“…(Karthik et al, 2014b). LAMP assay for specific diagnosis of B. abortus was also developed which was 100 fold more sensitive than the commonly employed PCR (Karthik et al, 2014c). Severity of bone damage in cases of poll evil and fistulous withers can be identified by radiography.…”
Section: Serological Tests Like Rose Bengal Plate Test (Rbpt) Standamentioning
confidence: 99%
“…(Karthik et al, 2014b). LAMP assay for specific diagnosis of B. abortus was also developed which was 100 fold more sensitive than the commonly employed PCR (Karthik et al, 2014c). Severity of bone damage in cases of poll evil and fistulous withers can be identified by radiography.…”
Section: Serological Tests Like Rose Bengal Plate Test (Rbpt) Standamentioning
confidence: 99%
“…; Karthik et al . ). The advantage of LAMP, in comparison to PCR‐based methods, is its low susceptibility to inhibition by contaminants present in DNA or RNA samples.…”
Section: Discussionmentioning
confidence: 97%
“…Patel et al, (2015) and Karthik et al, (2014) used species specific +IS711 primers for detection of Brucella abortus and they yielding 498bp band and Vizcaino et al, (1996)used species specific omp31 primers for detection of B. melitensis and they yielding 723bp band when electrophoresed through 2% agarose gel. Lopez Goni et al, (2008) reported Bruce-ladder was species specific and all the strains and biovars from the same Brucella species gave the same profile.…”
Section: Molecular Detection Of Brucella From Clinical Samplesmentioning
confidence: 99%